Enhancing EFL College Students’ Language Performance via eBook Supported Learning (International Conference on Computers in Education, 2019)
This study aims to analyze which particular learning behaviors with eBook supported learning are associated with high-achievers in language learning. This specifically focuses on English output (refers to English writing in this study) performance. Furthermore, to compare learning with and without an eBook, this study observes the correlation between self-regulated English learning (SREL), English self-efficacy (ESE), and learning achievements. This is done as a means to suggest which particular form of learning autonomy awareness should be explicitly addressed to boost language learning outcomes. This semester-long study was conducted with EFL students from the College of Management in a “General English for Specific Purposes” (GESP) course in a four-year comprehensive university in Taiwan. Pre-class reading materials were uploaded to an eBook platform and features of the platform were introduced beforehand to facilitate self-learning prior to class. Through analyzing the students’ 1) learning logs on the eBook platform, 2) scores on SREL and ESE questionnaires, and 3) learning achievement, the results revealed that online reading behaviors of adding markers and memos had a significant, positive correlation with students’ learning achievements. Meanwhile, the experimental group students outperformed those in the control group in open-ended, short essay style questions in terms of written statement quantity. With regards to SREL, scores in both the control and experimental groups increased throughout the study.